2007
DOI: 10.1007/s11160-007-9070-x
|View full text |Cite
|
Sign up to set email alerts
|

Resource allocation in yolk-feeding fish

Abstract: An insight is made into the main processes that occur in fish during endogenous feeding period. The ways in which yolk absorption rate can be measured are evaluated. Essential amino acids and polyunsaturated fatty acids are preferentially retained for incorporation into body tissue. Profound physiological and anatomical changes in yolk and a sequence of slow, fast, and a second period of slow absorption occur during the endogenous feeding period. Attempts to quantify the ontogenetic sequence are reviewed. Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
175
2
15

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(207 citation statements)
references
References 234 publications
(478 reference statements)
9
175
2
15
Order By: Relevance
“…These studies can characterize the most important events during development, such as the total consumption of the yolk sac, the appearance of internal and external structures, mouth opening, and other characteristics (Sato et al, 1998;Nakatani et al, 2001;Sato et al, 2003;Borçato et al, 2004;Kamler, 2008). For carnivorous species, the exact timing of the mouth opening is important to indicate the time that the animal, until then considered to be within a closed system, enters into an open system, and therefore begins exogenous food intake.…”
Section: Discussionmentioning
confidence: 99%
“…These studies can characterize the most important events during development, such as the total consumption of the yolk sac, the appearance of internal and external structures, mouth opening, and other characteristics (Sato et al, 1998;Nakatani et al, 2001;Sato et al, 2003;Borçato et al, 2004;Kamler, 2008). For carnivorous species, the exact timing of the mouth opening is important to indicate the time that the animal, until then considered to be within a closed system, enters into an open system, and therefore begins exogenous food intake.…”
Section: Discussionmentioning
confidence: 99%
“…First, under hypoxia, tissue differentiation rates can retard development, so that embryos from males kept in hypoxia may be at earlier stages of development resulting in smaller sizes [67,68]. Second, development may progress at similar rates but embryos are smaller due to less efficient anaerobic metabolic processes [69,70]. Third, quality of parental care (for instance, nutrients provided) may differ in normal and low O 2 conditions owing to the physiological stress imposed by hypoxia on the caring parent, affecting the Table 3.…”
Section: (B) Oxygenationmentioning
confidence: 99%
“…Effects of first feeding time on larval growth performance During endogenous feeding period, larvae may decrease absolute metabolic rate and show depressed growth under starvation, even before final yolk absorption (Kamler 2008). The results showed that larval growth of Chinese perch was sensitive to the timing of first feeding.…”
Section: Discussionmentioning
confidence: 94%
“…This might be due to the following three main reasons. First, the absolute metabolic rate has increased to a peak at the time of first feeding (Kamler 2008). Second, the digestive systems of Chinese perch larvae become functional immediately after first feeding (Wu et al 2007).…”
Section: Discussionmentioning
confidence: 99%